The effects of social distancing and self-isolation during the COVID-19 pandemic on adults diagnosed with asthma: A qualitative study. (May 2022) - Tyson, Leanne; Hardeman, Wendy; Stratton, Gareth; Wilson, Andrew M; Semlyen, Joanna
This study aimed to explore how social distancing and self-isolation measures, aimed at protecting vulnerable groups from COVID-19, affected the wellbeing and physical activity levels among adults diagnosed with asthma. Twenty-seven participants took part across four online focus groups. Transcripts were analysed using thematic analysis. Participants reported becoming more health conscious due to being labelled as vulnerable. Their relationship with the severity of their asthma was altered and they reported making positive changes to increase their physical activity levels. Findings suggest there is a window of opportunity to engage with people diagnosed with asthma to promote beneficial lifestyle changes and self-management.